Fake news pattern recognition using linguistic analysis - Dey, Amitabha; Rafi, Rafsan Zani; Hasan, Shahriar; Kundu, Sauvik (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.